MINDFULNESS-BASED APPROACHES IN NURSING: A COMPREHENSIVE SYSTEMATIC REVIEW - Iikura, Atsumi; Tamura, Haruka; Miyamoto, Shohei; Sugawara, Daichi (Universitas Nahdlatul Ulama Surabaya, 2025)
Introduction: Nurses have encountered significant stress, especially during the COVID-19 pandemic. While previous meta-analyses evidenced the efficacy of mindfulness in addressing negative mental states among nurses, the positive effects remain less clear. Objective: This study aims to systematically review previous literature on mindfulness interventions and examine their impact on stress, burnout, mental health, and quality of life among nurses. Design: Systematic literature review following PRISMA guidelines. Data Sources: Seven databases (Web of Science, MEDLINE, Science Direct, CINAHL, Cochrane, Ichu-shi, J-STAGE) were searched for randomized control trials (RCTs), non-RCTs, and qualitative studies published before October 2021 in English or Japanese. Review Methods: The review protocol was registered in PROSPERO (CRD42021269307). Studies were screened, selected, and appraised for quality using Joanna Briggs Institute checklists. Data were extracted and synthesized narratively. Results: Sixty studies met the inclusion criteria. Interventions were heterogeneous in format, duration, and delivery. While overall study quality was moderate, results showed significant correlations with psychological variables. Both positive (e.g., well-being, self-compassion) and negative (e.g., stress, burnout) outcomes were reported. Conclusions: Mindfulness interventions offer potential benefits for nurses, though further research with standardized designs and outcomes is needed. Qualified instructors and structured implementation are essential to ensure effectiveness and safety.